Associations of CTLA4 Gene Polymorphisms with Graves’ Ophthalmopathy: A Meta-Analysis - Pengfei Du; Xiaojie Ma; Changjiang Wang (International Journal of Genomics)
Many studies have established that T-lymphocyte antigen-4 (CTLA4) is a susceptible gene for Graves’ disease (GD). Also many studies showed the association between the CTLA4 exon-1 49A/G polymorphism and the risk of developing Graves’ ophthalmopathy (GO) in GD patients. But those results were inconsistent. In recent years many new studies were published which helped to shed light on the relationship of CTLA4 SNP49 with GO. So we performed the meta-analysis to explore the association between the SNP49 and GO susceptibility in GD patients. Studies up to February 29, 2012, were searched by using PubMed. The odds ratio was used to evaluate the strength of the association. Altogether 12 case-control studies involving 2,505 participants were included in the meta-analysis. Results showed that the G allele was related to the increased risk of GO compared with the A allele under allelic genetic model (OR = 1.14, 95% CI: 1.14–1.72, P=0.001) in European subgroup. No publication bias was detected. Our results showed that the SNP49 polymorphism of CTLA4 gene was related to increased risk of GO.